Task Assignment over the Business Cycle - Devereux, Paul J. (Journal of Labor Economics, 2000)
In this article, I evaluate the hypothesis that firms respond to negative demand shocks by assigning workers to tasks that require less skill than the tasks they normally carry out. Using changes in employment in state‐industry cells as a measure of demand conditions facing individual firms, I provide evidence in favor of the hypothesis. Furthermore, the skill requirements of the tasks carried out by workers are procyclical. The results are consistent with a specific capital model where employers move workers between tasks so that layoffs are concentrated on workers with low levels of firm‐specific human capital.